Black sands, green plans and vernacular (in)securities in the contested margins of south-western Madagascar. (4th May 2017) - Huff, Amber
Abstract: This article explores a contradiction at the heart of the environmental security–development nexus by bringing conceptual and political logics of environmental security into critical dialogue with vernaculars of security and insecurity in the 'margins' of rural southwestern Madagascar. The analysis presented here highlights important ways in which state–society relations are transformed as development intersects with historical patterns of resource access and alienation, and legacies of disenfranchisement and violence. Analyses of secondary literature, national policy and results of ethnographic research conducted in southwestern Madagascar since 2007 reveal a stark disjuncture between dominant logics of environmental security that guide exclusionary conservation and resource developments and situated understandings and experiences on the ground. Understanding contemporary resource conflicts and building peace requires a broadening of the notion of conflict, methodological deepening as well as a shift in institutional cultures to expand types of knowledge and actors' perspectives that are privileged and legitimised in both scholarship and policy-making.